Astrocytes: Role and Functions in Brain Pathologies - Siracusa, Rosalba; Fusco, Roberta; Cuzzocrea, Salvatore (Frontiers in Pharmacology, 2019)
Astrocytes are a population of cells with distinctive morphological and functional characteristics that differ within specific areas of the brain. Postnatally, astrocytes progenitors migrate to reach their brain area and related properties. They have a regulatory role of brain functions: are implicated in neurogenesis, synaptogenesis, controlling blood-brain barrier permeability and maintaining extracellular homeostasis. Mature astrocytes also express some genes enriched in cell progenitors, suggesting they can retain proliferative potential. Considering heterogeneity of cell population, it is not surprising that their disorders are related to a wide range of different neuro-pathologies. Brain diseases are characterized by the active inflammatory state of the astrocytes, which is usually described as up-regulation of glial fibrillary acidic protein (GFAP). In particular, the loss of astrocytes function as a result of cellular senescence could have implications for the neurodegenerative disorders, such as Alzheimer disease and Huntington disease, and for the aging brain. Astrocytes can also drive the induction and the progression of the inflammatory state due to their Ca2+ signals and that it is strongly related to the disease severity/state. Moreover, they contribute to the altered neuronal activity in several frontal cortex pathologies such as ischemic stroke and epilepsy. There we describe the current knowledge pertaining to astrocytes role in brain pathologies and discuss the possibilities to target them as approach toward pharmacological therapies for neuro-pathologies.